Antimitoic Peptides: Synergistic Anticancer Effect of Peptide‐Docetaxel Nanoassembly Targeted to Tubulin: Toward Development of Dual Warhead Containing Nanomedicine (Adv. Healthcare Mater. 2/2017). Issue 2 (January 2017) - Mohapatra, Saswat; Saha, Abhijit; Mondal, Prasenjit; Jana, Batakrishna; Ghosh, Subhajit; Biswas, Atanu; Ghosh, Surajit
Abstract : In article 1600718, Surajit Ghosh and co‐workers describe the development of a highly bioavailable novel breast cancer cell specific liposomal nano‐vesicle, which contains combination of microtubule targeted therapeutics such as docetaxel and tubulin targeted peptide. It causes severe intracellular microtubule depolymerization, significant synergistic apoptotic death, inhibition of migration of triple negative metastatic cancer cell and reduction of tumor mimicking 3D spheroid growth.